St. Kitts and Nevis : Fourth Review Under the Stand-By Arrangement, Financing Assurances Review and Request for Waivers of Applicability-Staff Report and Press Release. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
Economic activity continued to shrink in St. Kitts and Nevis in 2012 on account of a sharp slowdown in the construction sector. Despite the sluggish global environment, the authorities have continued to successfully implement their economic program. Inflation has stabilized. The external position is relatively stable since the improved trade balance. Bank credit is restrained by the sluggish economy and rising nonperforming loans (NPLs). Despite the continued economic contraction, all of the fiscal targets are met owing to strong non-tax and income tax receipts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet